A rare case of group A streptococcal toxic‐shock syndrome in a postpartum adolescent leading to multi‐organ failure. Issue 5 (16th March 2020) - Cortez Granados, Samuel; Batsch, Jonathan; Lui, Asona; Hessman, Jacob; Gloyeske, Nika; Panchal, Apurva
Abstract: Teenage pregnancy is not uncommon, but given the age of the patient, experience, and competency among medical providers varies. While toxic‐shock syndrome from group A streptococcus is rare in teenage pregnancy, observed is a gap in care of bridging. Abstract : Teenage pregnancy is not uncommon, but given the age of the patient, experience, and competency among medical providers varies. While toxic‐shock syndrome from group A streptococcus is rare in teenage pregnancy, observed is a gap in care of bridging.